Methodology for selecting and implementing priorities for smart regional specialization - N. P. Ivashchenko; A. А. Engovatova; A. A. Bogdanenko (Модернизация, инновация, развитие)
Purpose: is to develop the methodology for identifying long-term priorities for smart specialization in the regions and creating "transformational roadmap" for their implementation in the Russian context. This approach is designed to foster sustainable innovation ecosystems and achieve the country’s technological sovereignty.Methods: the research is based on the comparative analysis of international experience in implementing regional innovation policies and smart specialization strategies in the EU, the USA, and China. The study employs qualitative, systemic, and structural-logical analysis methods. The proposed methodology draws on the experience of regional strategy development and a series of expert interviews with representatives of regional authorities.Results: the authors propose the methodology for applying the smart specialization concept in the Russian regions, structured into four key stages: selecting smart specialization priorities, assessing regional potential for industry transformation, forming a portfolio of projects, and their implementation. Additionally, the study systematizes approaches to identifying the potential for smart transformation and selecting suitable projects within a region. Special attention is given to the process of "entrepreneurial discovery" and the development of "transformational roadmaps", which integrate both scientific and technological priorities and the unique characteristics of the regions.Conclusions and Relevance: the proposed methodology enables Russian regions to systematically and structurally organize the process of defining innovation development priorities, aligning both with national strategic goals for technological leadership and local specificities. This contributes to the formation of sustainable innovation ecosystems, the integration of science, business, and government, and the achievement of technological sovereignty. The practical significance of the study lies in the applicability of the methodology for developing regional smart specialization strategies, which can serve as a foundation for long-term economic growth and national competitiveness in emerging markets.